The Effect of Marketing Mix on Purchase Decisions of Nmax Motors at Yamaha Manna Dealers in South Bengkulu Regency - Yeti Hamlaini; Tito Irwanto; Yudi Irawan Abi (Penerbit Jurnal Indonesia, 2022)
Two-wheeled vehicles such as motorcycles are a necessity for humans in their daily activities. By having a motorbike, we can do activities quickly and easily so that it is not hampered and hindered from work. The purpose of the study was to determine the effect of product, price, location and promotion on purchasing decisions for Nmax motorcycles at Yamaha Manna Dealers, South Bengkulu Regency.This type of research is using quantitative research. Quantitative approach is a research method based on the philosophy of potivism, used to examine a particular population or sample. Researchers took non-probability samples selecting several people who were considered to be able to represent the population, which amounted to 45 consumers.The results of the multiple linear regression analysis are Y = 12.344 + 0.101 X1 + 0.390 X2 + 0.132 X3 + 0.104 X4, this describes a positive regression direction, meaning that the product variable (X1), price (X2), location (X3) have a positive influence. on purchasing decisions (Y) at the Yamaha Manna Bengkulu Selatan Dealer. The value of the coefficient of determination from the results of calculations using SPSS can be seen that the value of the coefficient of determination from R square is 0.623. This means that the product value (X1), price value (X2), location (X3) and promotion (X4) affect purchasing decisions (Y) by 62.3% while the remaining 37.7% is influenced by other variables not examined in this research.